Efeitos de uma terapia fonoaudiológica em grupo de professores com distúrbio de voz - Pereira, Mariane Maião (2021)
Introduction: the Technical Section of Speech Therapy. of the Hospital do Servidor Público Municipal de São Paulo (HSPM) receives an approximate number of 30 people / month, with reports of vocal changes. This search, which has been taking place for 29 years, resulted in the creation of a Voice Program at the institution. held every six months, in five groups composed of up to 15 teachers with a duration of 15 meetings / weekly. Objective: to analyze the effects of group speech therapy on self-reported vocal symptoms and the self-report of teachers with voice disorders. Method: this intervention analysis study (pre and post) was approved by the Ethics Committee of PUC-SP (CAAEnº 18756319.0.0000.5482) and of the Hospital do Servidor Público Municipal de São Paulo (CAEE nº 18756319.0.3001.5442) and counted with teachers, with voice disorders seen in the Voice Program of the referred hospital (second semester of 2019). After the inclusion criteria were established, 23 teachers were analyzed by means of otorhinolaryngological (diagnosis) and speech-language evaluation of the voice (survey of health and treatment aspects, GRBASI scale, pitch, loudness, resonance, respiratory type and pneumophonoarticulatory coordination) and responses Vocal Handicap Index (IDV), Voice Disorder Screening Index (ITDV), Teacher Vocal Production Conditions (CPV-P), ITDV, Vocal Fatigue Index (IFV), Self-Report on Voice (ARSV- Initial and ARSV-Final). Descriptive record presented the effects according to the participants' selfreport and the statistical analysis compared the scores of the ITDV and IFV instruments before and after the intervention. Results: the group, entirely female, had a median age of 45 years, 6 to 10 hours / day of workload, working in two schools / periods. The participants presented changes in the larynx and voice. They made reference to factors that interfere in vocal production, arising from the environment and work organization. All of these data led teachers to register vocal handicap. When comparing the pre and post data, the ITDV registered a statistically significant difference with a decrease in the total of mentioned symptoms (mean from 10 to 7.6 = p <0.001), and for the occurrence of clearing, dry cough, cough with secretion and pain when swallowing (p <0.050). However, no difference was found when considering the clinical cutoff point determined by the instrument (≥ 5 symptoms). The score referring to the general mean of the IFV domains was lower at the moment after the intervention (significant difference), with emphasis on the positive and statistically significant reduction (p <0.005) for the variables “I have to work hard to produce the voice after I spoke a little more ”,“ I have difficulty projecting my voice while I speak ”,“ When I speak a lot I feel pain to speak ”and“ When I speak my throat hurts ”presented The analysis of self-reports showed that most teachers, when finalize the program, said he observed changes in his voice, mentioning aspects related to his habits / care with the voice (60.9%; n = 14), but they said there was a need to establish discipline to put the worked content into practice (56.5%; n = 13) Conclusion: the record of reduction in vocal symptoms, especially those related to vocal fatigue, accompanied by a positive self-report regarding the change in habits were recorded after the completion of the Voice Program. The managers of that Program must be attentive to establish the possibility of continuing the process with actions that may help teachers to actually incorporate the practices learned in their daily lives